2017
DOI: 10.1177/2150131917742299
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of Human Papillomavirus Vaccination and Its Associated Factors Among Adolescents: A Systematic Review

Abstract: Background: The purpose of this review was to explore the uptake of the human papillomavirus (HPV) vaccination, its associated factors, and the facilitators of and barriers to HPV vaccination among adolescents. Methods: A comprehensive literature search was conducted through 5 electronic databases, including PubMed, CINAHL, Cochrane Library, Medline, and PsycInfo from January 2006 to March 2015 for studies examining the uptake, awareness, knowledge, acceptability, and intention of adolescents with regard to HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(193 citation statements)
references
References 54 publications
6
166
6
1
Order By: Relevance
“…The extent to which individual-level determinants including demographics, clinical or provider characteristics, state of residence, and vaccine mandates, as well as state-level determinants such as the number of pediatricians per 10,000 persons aged 0-18 years, state health-care expenditures, education mandates and IIS utilization, were associated with the likelihood of MenACWY vaccination was assessed to further investigate potential determinants of these differences in completion and compliance. While other studies have assessed determinants of vaccination in adolescents, 26,27 to our knowledge, this is the first study to investigate MenACWY vaccine primary and booster dose completion and compliance with ACIP recommendation using multi-level modeling to determine the impact of state-level factors in addition to individual-level factors.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which individual-level determinants including demographics, clinical or provider characteristics, state of residence, and vaccine mandates, as well as state-level determinants such as the number of pediatricians per 10,000 persons aged 0-18 years, state health-care expenditures, education mandates and IIS utilization, were associated with the likelihood of MenACWY vaccination was assessed to further investigate potential determinants of these differences in completion and compliance. While other studies have assessed determinants of vaccination in adolescents, 26,27 to our knowledge, this is the first study to investigate MenACWY vaccine primary and booster dose completion and compliance with ACIP recommendation using multi-level modeling to determine the impact of state-level factors in addition to individual-level factors.…”
Section: Discussionmentioning
confidence: 99%
“…PeopleÂŽs intention to vaccinate against HPV is a factor that contributes to the acceptance of the vaccine. Thus, many studies have been carried out to research the determinants of HPV vaccine acceptance [10][11][12][13]. In this sense, the fact that HPV vaccines are aimed at adolescents raises the following issues: a) there may be important barriers to access preventive health services for this population subgroup, and b) caregivers opinions affect adolescents' vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the fact that HPV vaccines are aimed at adolescents raises the following issues: a) there may be important barriers to access preventive health services for this population subgroup, and b) caregivers opinions affect adolescents' vaccination. The studies on this subject have been carried out in high-income countries, where potentially associated factors such as perception of risk, awareness and knowledge of HPV, and recommendation source, among others, have been assessed [13]. Latin America countries such as Colombia, Mexico, and Brazil have studied HPV vaccine acceptability, finding that it varied depending on the social context characteristics and that knowledge of the HPV vaccine was an important determinant for its acceptability [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to a person's unwillingness to be aware of the disease and its vaccine, on the other hand, due to the culture and values of the society where talking about sex is thought taboo. Many studies have also reported that lack of HPV vaccine uptake is due to a lack of knowledge about the vaccine and related cancer in men and women [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%